EVALUATION OF THE EFFICIENCY AND QUALITY OF THE TRAM ROUTE OF SETIF CITY, ALGERIA: COMBINING AHP AND GIS APPROACHES - Salim Dehimi; Ibrahim Djouani; Ali Redjem (université msila, 2022)
The study aims to evaluate the efficiency of the tram track in the urban transport system of the Algerian city of Setif by combining Analytical Hierarchy Process (AHP) and Geographic Information System (GIS) approach. In this research, a set of multiple pre-determined criteria applicable in the field of urban transport were selected for decision-making. They were collected from recent research literature and expert opinions in this discipline, and then were arranged and evaluated in the AHP to extract the main weights for each criterion. In the end, they were processed spatially by using GIS. The study showed that the selection of the tramway track in the city of Setif was not successful in terms of the chosen location, and its selection was not studied according to the efficiency and quality criteria applicable in the field of urban transport. In addition, the study concluded that there is a significant shortfall in the first tram track, especially the one linking the tram route to the northern and southern parts of the city, which affected the efficiency and quality of the tram route. As the results have shown, the percentage of good spaces near the tram route does not exceed 0.34%. It is followed by the percentage of the average and acceptable areas (13.48%) and then the percentage of the marginalized areas and the areas far from the tram track (86.18% of the total area of the city). The study also demonstrated the importance of using AHP and GIS in evaluating a completed tram track according to a comprehensive and widely studied scientific methodology.
Keywords: urban transport; transport decision-making; AHP; GIS; tramway Setif